Figure 6 in Recent evolution of ancient Arctic leech relatives: systematics of Acanthobdellida - Carle, Danielle Božena De; Gajda, Łukasz; Bielecki, Aleksander; Cios, Stanisław; Cichocka, Joanna M.; Golden, Heidi E.; Gryska, Andrew D.; Sokolov, Sergey; Shedko, Marina Borisowna; Knudsen, Rune; Utevsky, Serge; Świątek, Piotr; et al. (Zenodo, 2022)
Figure 6. Scanning electron micrographs of general morphology in small specimens. A, Acanthobdella peledina (4 mm; Alaska). B, Paracanthobdella livanowi (3.5 mm; Kamchatka). Single black arrows, anterior body region; double black arrows, posterior sucker. In the A. peledina specimen, some fragments of host tissue (white arrow) are still attached to the sucker. Published as part of Carle, Danielle Božena De, Gajda, Łukasz, Bielecki, Aleksander, Cios, Stanisław, Cichocka, Joanna M., Golden, Heidi E., Gryska, Andrew D., Sokolov, Sergey, Shedko, Marina Borisowna, Knudsen, Rune, Utevsky, Serge, Świątek, Piotr & Tessler, Michael, 2022, Recent evolution of ancient Arctic leech relatives: systematics of Acanthobdellida, pp. 149-168 in Zoological Journal of the Linnean Society 196 on page 161, DOI:10.1093/zoolinnean/zlac006, http://zenodo.org/record/7037718